The Representation of Black Feminism in Hidden Figures (2016) - Andhika Cikal Rustananto, 121411231106 (2018)
In the 1960s, African-American were always represented in various movies as a simple ethnicity group regardless of their gender, religion, or cultural backgrounds. But in this 2017 movie entitled Hidden Figures, African-American people were portrayed to have intersecting layers within their community, mainly between gender and race. This paper intended to dissect the representation of African-American women archetype that displayed by the central figures of this movie through their narrative background. By making a good use of Hall’s Theory of Representations and supported by the concept of Intersectionalism coined by Kimberle Crenshaw, this study used film analysis and qualitative method approach to analyze the data. Based on the narrative and non-narrative qualitative analysis, the data is gathered by selecting several major scenes that contributed to this movie, to be applied in conjunction with the theory, in order to gain findings. From the data, it can be concluded that each of the three main characters in the movie easily fell on the African-American woman stereotype, namely Mammy, Jezebel, and Sapphire. This study can potentially add a new insight on how to notice an intersecting pattern of oppression while also open the eyes of society that oppression does not come from one way only, but also from several layers and directions. The field of intersectionality and black feminism has already vast enough, but this study can add to the list of media that representing the intersectionality into the recent era. They can progress through the field in such a way that movie interpretations of black feminism and intersectionality have become possible.